PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KINERJA APARATUR PEMERINTAH DAERAH DENGAN JOB RELEVANT INFORMATION SEBAGAI MODERASI DI KABUPATEN KONAWE - Nalise, Nalise; Mas'ud, H Arifuddin; Abdullah, Muntu (JPEP (Jurnal Progres Ekonomi Pembangunan), 2019)
This research aimed to knowing the effect of Budgeting Participation toward the performance of the Local Government Apparatus with Job Relevant Information as Moderation Variables in Konawe district. The population of this research was all the staff on echelon III and echelon IV at OPD in government environment of Konawe District amount to 573 respondents, while the sampling was purposive sampling technique. The respondents of this research have criteria, such as : 1) The apparatus which have position as Head of Division/Secretary, Head of Sector, Head of Programmer and Finance; 2) Had been occupied the position at least 1 year. The research respondents of this research was 211 people. Technique of analyzing data used was moderated analysis regression and Soft IBM SPSS Statistics 23 as support.The results of the research showed that (1) Budgeting Participation give positive and significant effect toward the Performance of the Local Government Apparatus in Konawe district with t count was 7.893 and significant was 0.00<0.05; (2) Job relevant Information cannot have a role as variable which moderated the effect of Budgeting Participation toward the Performance of the local Government Apparatus of Konawe District with with t count was 1.187 and a significancy was 0.237>0.05. Conclusion : 1) The higher the level of budgeting participation will improve performance of the Local Government Apparatus; 2) The higher job relevent information in budgeting participation, then in tends to reduce the performance of local government apparatus in Konawe district.Â Key Words:Â  Budgeting Participation, Job Relevant Information